Web-Based E-commerce Design Using the Waterfal Method - Dede Eko Saputro; Andrian Hidayat; Muhamad Rosdiana (bit-Tech, 2025)
Current advancements in digital technology have transformed transaction and sales activities, yet CV. Mella Vista still relies on manual processes that limit information accessibility and reduce operational efficiency. Responding to this limitation, the study aims to develop a structured web-based e-commerce system that enhances promotional reach, transaction processing, and administrative reporting. The system was designed using the Waterfall method, incorporating sequential phases of analysis, design, implementation, and testing, and implemented using PHP and MySQL to ensure stable data management and functional reliability. Through this approach, the research provides a clear methodological foundation for developing a system aligned with organizational needs. The resulting e-commerce platform offers real-time product visibility, streamlined ordering procedures, and automated reporting features, addressing the reviewers’ emphasis on clarifying methodological contribution and system capabilities. Empirical testing demonstrates that the system operates effectively across key functions—user authentication, product display, cart management, checkout, and payment verification—supporting accuracy and ease of use for both administrators and customers. Quantitative evaluation shows that sales increased from 6,577,500 in November to 8,795,000 in December, representing an approximate 33.7% improvement, thereby providing contextual clarity as requested by reviewers. This measurable gain indicates that the system not only enhances data processing efficiency but also strengthens customer engagement and purchasing activity. Overall, the findings confirm that the implemented e-commerce system significantly improves operational effectiveness, increases informational transparency, and supports stronger competitive positioning, offering a practical digital solution for small enterprises seeking to modernize their sales processes.